Towards a new policy direction for an improved housing delivery system in Nigerian cities: Theoretical, Empirical and Comparative Perspectives - Gbadegesin, Job Taiwo (A+BE | Architecture and the Built Environment, 2018)
In Nigeria, housing units are not adequate for the entire population, especially in cities (Anosike et al. 2011, Makinde 2014). For instance, the deficit grows at an alarming rate, from about 8 million in 1991 to over 16 million in 2000s (Aribigbola, 2000; Aribigbola and Ayeniyo 2012). The challenges of housing provision are not only quantitative but also qualitative and have to be dealt with in a dual institutional perspective: the formal and the informal sector (Makinde, 2014; National Population Census, NPC, 2006). How can the Nigerian housing provision be improved and what are the new roles that policy can play to address the housing shortages in Nigerian cities? Several researchers have examined the subject of housing in Nigeria and confirmed the existence of shortages. Some have also attempted to advocate that there are challenges without giving an appropriate policy way forward. Also, most of the existing studies are not based on appropriate theoretical underpinnings. Therefore, this thesis contains a diagnosis of the housing problems in Nigeria, based on the nature of the housing provision systems (formal and informal) and a framework for possible policy solution(s), using theoretical, empirical and comparative approaches. Emphasis was placed on the theoretical and empirical perspectives, while an insight was gained into possible solutions adopted in some selected countries through a synthesis of extant studies. To capture the actual contexts of housing challenges, six objectives raised in the form of research questions were pursued. In the first objective, the Nigerian housing situations were examined in the contexts of political, economic and demographic developments in order to identify the nature of the housing shortages. Findings from the first objective indicated that housing shortages in Nigerian cities are both quantitative and qualitative in nature. The major problems were found in the informal sector because the formal sector is not accessible due to changes in government administration, the low income condition and institutional barriers. It was found that the decline in the formal provision resulted in the growth of the informal provision. Against the backdrop, new institutional economics, NIE theoretical approach was embraced owing to the fact that Nigerian property market constitutes formal and informal institutions, and fraught with non-availability of data (Omirin and Antwi, 2004). This is central to the second objective. With the adoption of NIE as the appropriate school of thought, the structure, institutions, agencies, strategies, interests, and how these elements are connected to housing delivery could be examined, using an appropriate analytical framework, based on factors of production. Subsequently, the structure of housing provision was examined over the pace of time. Because the influence of government was identified in the structures, objective four elaborates on the actual roles, the units of housing provided by the government and the changing roles of the government. The research question five is the central focus of this dissertation where the strategies of procuring factors of production, (land, labour, materials and finance) were examined. Housing outputs, its management, institutional environment, structure, transactions, motivating factors and the existing challenges were examined. The main findings include inadequacy of finance and the complexity of securing formal funds are key to decent housing provision by individual formal providers, from the pre-construction to post-construction stage. There are also difficulties of acquiring land and securing it, due to threat of Omo-oniles (families of the customary owners who often lay claims to land). In addition, formal system is only accessible to higher income groups and inaccessible to lower class in Nigeria Since the formal market cannot be easily accessed by many people, low income groups rely on the informal sector. In the informal finance system, member of a financial association mandatorily saves an agreed amount, within the limit of his/her income capacity, and augments it with personal or family funds. One of the motivations behind these informal group finance systems is that they serve as saving mechanisms for the people. Other production factors, such as human and material resources, are equally procured in an informal manner either through family members or by friendly arrangements and instalment agreements in order to avoid the complex hurdles identified in the formal system, e.g. transaction hurdles. To gain insight into other countries with similar housing experiences, a review of the situation in South Africa, Brazil and Mexico was done. In South Africa, existing studies and existing policy documents revealed that various policy approaches were adopted. I found in the review that the perceived improved performance in transforming informal housing is attributed to the joint cooperative, participatory approach and political support through legal instruments. I observed that policy approaches in Brazil are channelled towards addressing informal housing. The review of existing literature and documents revealed that legal instruments have been the intervening tool in the context of the regularisation goals, which includes legalisation, recognition of tenure rights, upgrading and provision of services/amenities (urban management). These exercises could only be executed within the broader, integrated, multi-sectoral scope of city and land use planning, concurrently implemented and recognition of politico-institutions, i.e. the involvement of a cooperative government, informal residents, NGOs and private developers with substantial technical, managerial and financial support. In Mexico, regularisation projects, through an extensive land titling programme, taxation instruments and planning tools, made it a result-oriented land regularisation programme in the developing world, as indicated by Monkkonen (2012). Mexico’s approach is known for its recorded successes, however, it is not without challenges. It was also mentioned that the whole process commenced from the ejido system, which indicates an integration of communities and civil societies into the land system. Mexico has also attempted to incorporate informal housing finance institutions on a limited level into mainstream financial institutions (FONHAPO and SOFOLES). The point is that the land titling process, in collaboration with agencies and NGOs in procuring production factors, contributes significantly to progress in some cities. Nevertheless there is still room for improvement. Having examined the strategies, their motivations and the challenges, it was recommended that a combination of suggested possible solutions and lessons from the three selected countries resulted in a comprehensive solutions framework which includes the following recommendations: Review of Land Use Act (LUA) of 1978 to incorporate both customary and statutory systems in order to resolve Omo-onile crisis. Ensuring prompt tilting of land of existing informal houses at a low cost. Upgrading the existing informal settlements/housing with joint consent of the owners or the occupiers and ensuring their socio-economic empowerment. Introducing, implementing and government monitoring of housing subsidies for development and maintenance. Formulating policies and educating new home owners ( both owner-occupied and rental housing owners) to comply with building codes for safety reasons. Government should implement and manage affordable housing that can lead to social housing. Government should be involved in making cooperative societies formal and embraced PPP agenda that can touch low income groups.